Penalaran Rasional dan Maslahah: Ijtihad Umar ibn al-Khattab pada Kasus-Kasus Kewarisan Islam: Penalaran Rasional dan Maslahah: Ijtihad Umar ibn al-Khattab pada Kasus-Kasus Kewarisan Islam - Yusron, Muhammad (Institut Agama Islam Negeri (IAIN) Pontianak, 2021)
The provisions of Islamic inheritance have been regulated in such detail and specific in the Qur’an and hadīth. However, several cases of Islamic inheritance produced by Umar ibn al-Khattab seem to contradict the provisions of the naṣh. This paper is a literature study with a normative-juridical study approach that aims to describe and analyze the results of Umar ibn al-Khattab’s ijtihād in inheritance cases that are ijtihādiyyah. This study indicates that the results of Umar ibn al-Khattab’s ijtihād in resolving inheritance cases are based on logical reasoning and are oriented to benefit (maslahah). This matter can be evidenced by giving 1/3 of the remaining part to the mother in the gharawain case, the unification of the inheritance of a sibling with a half brothers or sisters in the musytarakah case, and other inheritance cases such as ‘aul, radd, and inheritance of grandparents. Umar always prioritizes rational reasoning and maslahah in his interactions with naṣh. For him, a law is very much tied to the context of when and where it is enacted. Differences in time and place in the determination of law affect the results of ijtihād.